Pengaruh Strategi Model Kooperatif terhadap Peningkatan Partisipasi dan Hasil Belajar Manipulatif Siswa Perempuan dalam Pendidikan Jasmani di SD - Giat Akbar Maulana; Mustika Fitri; Tite Juliantine (Universitas Pendidikan Indonesia (UPI), 2020)
Abstract This research is motivated by the low participation of female students in physical education learning (Goodyear, Casey, Kirk, 2014). The purpose of this study is to determine the increase in participation and manipulative learning outcomes of female students in physical education in fifth grade students of SDN 053 Cisitu, Bandung City 2019/2020. Therefore, researchers are interested in conducting a study so that participation and manipulative learning outcomes of female students can increase. In this study, researchers used an experimental research method with the research design used was The Matching-Only Pretest-Postest Control Group. The research instrument used the PEPAS -Purposes for Engaging in Physical Activity Scale questionnaire and the manipulative learning outcomes assessment sheet. Based on the results of the analysis it can be concluded that there is no difference in the effect of the three cooperative learning strategies on the participation of female students, so it can be said that the three strategies have the same effect in increasing the participation of female students. However, on the results of students' manipulative learning there are differences in the effects of these three cooperative learning strategies, where the STAD strategy provides the best effect on manipulative learning outcomes for female students, followed by the TGT strategy and the Jigsaw strategy. Abstrak Penelitian ini dilatarbelakangi oleh rendahnya partisipasi siswa perempuan dalam pembelajaran pendidikan jasmani (Goodyear, Casey, Kirk, 2014). Adapun tujuan dari penelitian ini yaitu untuk mengetahui peningkatan partisipasi dan hasil belajar manipulatif siswa perempuan dalam pendidikan jasmani pada siswa kelas V SDN 053 Cisitu Kota Bandung 2019/2020. Oleh karena itu, peneliti tertarik untuk melakukan sebuah penelitian supaya partisipasi dan hasil belajar manipulatif siswa perempuan dapat meningkat. Dalam penelitian ini peneliti menggunakan metode penelitian ekperimen dengan desain penelitian yang digunakan adalah The Matching-Only Pretest-Postest Control Grup. Instrumen penelitian menggunakan kuesioner PEPAS –Purposes for Engaging in Physical Activity Scale dan lembar penilaian hasil belajar gerak manipulatif. Berdasarkan hasil analisis dapat disimpulkan bahwa tidak ada perbedaan efek dari ketiga strategi pembelajaran kooperatif terhadap partisipasi siswa perempuan, sehingga dapat dikatakan ketiga strategi tersebut memberikan efek yang sama dalam meningkatkan partisipasi siswa perempuan. Akan tetapi, terhadap hasil belajar manipulative siswa terdapat perbedaan efek dari ketiga strategi pembelajaran kooperaif ini, dimana strategi STAD memberikan efek terbaik terhadap hasil belajar manipulative terhadap siswa perempuan, diikuti dengan strategi TGT dan strategi Jigsaw.